2009
DOI: 10.1248/bpb.32.1012
|View full text |Cite
|
Sign up to set email alerts
|

The Genome-Wide Expression Profile of Nelumbinis semen on Lipopolysaccharide-Stimulated BV-2 Microglial Cells

Abstract: This study was conducted to evaluate the protective mechanisms of Nelumbinis semen (NS) on lipopolysaccharide (LPS)-induced activation of BV-2 microglial cells. The anti-inflammatory effects of NS were determined by analyzing nitric oxide production and proinflammatory cytokines using enzyme-linked immunosorbent assay. The mechanism was evaluated in BV-2 cells with or without NS treated with LPS for various lengths of time using oligonucleotide microarray and real time reverse transcription-polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…In our case, BV2 cells were cultured under conditions expected to promote a resting state. We can confirm that as reported in the literature BV2 cells express Adora3 [59], Cnr2 [33,58], Mtnr1a [60], Galr2 [61], Ccr5, Cxcr3 [62] and Rgs2, 10, 12 [27,28,63]. We also detected mRNA for receptors that have been reported to be upregulated in response to stimulation such as Ccrl2 [28,64], Ptafr, Ptigr [64] and Rgs7 [65].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our case, BV2 cells were cultured under conditions expected to promote a resting state. We can confirm that as reported in the literature BV2 cells express Adora3 [59], Cnr2 [33,58], Mtnr1a [60], Galr2 [61], Ccr5, Cxcr3 [62] and Rgs2, 10, 12 [27,28,63]. We also detected mRNA for receptors that have been reported to be upregulated in response to stimulation such as Ccrl2 [28,64], Ptafr, Ptigr [64] and Rgs7 [65].…”
Section: Discussionsupporting
confidence: 90%
“…Here, too, we identified a few receptors that have been reported present for which we found levels of mRNA below the levels that we defined as statistically significant: Hcrtr1 [66], Gpr55 [58] and the receptor for Cx3cr1 [67]. We did not detect Prokr1 which is upregulated with activation [27], nor for Oprm1, P2ry1 and Gpr149 which are downregulated following activation [27,28]. Several reports have identified the presence of mGluRs in BV2 and primary microglia [21,68,69].…”
Section: Discussionmentioning
confidence: 91%
“…FGF12 gene expression has been shown to be induced in BV2 microglia in response to LPS [51], however no role for it has been described until this study. The main focus of FGF12 studies has been with its genetic alterations and associated epileptic changes through its ability to bind voltage-gated sodium ion channels [52, 53].…”
Section: Discussionmentioning
confidence: 82%
“…RASAL2 mutant mice had a drastic decrease in RASAL2 expression, impaired adipogenesis and lean phenotypes (4). Studies have also reported that RASAL2 may play a role in the isolation of cross-reacting antigen (5), creating a candidate vaccine against ticks (6) and lipopolysaccharide-induced activation of microglial cells (7). In addition, the function of RASAL2 can be regulated by microRNAs such as miR-136 (8).…”
Section: Introductionmentioning
confidence: 99%